Comparative portal hypotensive effects as propranolol of vitamin D3 treatment by decreasing intrahepatic resistance in cirrhotic rats. Issue 3 (March 2015) - Lee, Pei‐Chang; Yang, Ying‐Ying; Lee, Wei‐Ping; Lee, Kuei‐Chuan; Hsieh, Yun‐Cheng; Lee, Tzung‐Yan; Lin, Han‐Chieh
Abstract Background and Aim Vitamin D3 improves portal hypertension (PH) through the activation of vitamin D receptor (VDR) and calcium‐sensing receptor (CaSR) in cirrhotic rats. Propranolol is a non‐selective β‐blocker that is recommended for the treatment of PH. The present study aims to investigate the detail systemic and hepatic mechanisms of vitamin D3 and propranolol, alone or in combination, in cirrhotic rats. Methods Common bile duct‐ligated and thioacetamide cirrhotic rats were treated with vehicle, propranolol (30 mg/kg/day), vitamin D3 (0.5 μg/100 g/day, twice weekly), or propranolol + vitamin D3, separately. Results Significantly, propranolol and vitamin D3 produced a similar magnitude of reduction in portal venous pressure (PVP) in cirrhotic rats through different mechanisms: whereas propranolol decreased PVP by reducing splanchnic hyperemia and cardiac index, vitamin D3 decreased PVP by decreasing intrahepatic resistance (IHR). However, propranolol + vitamin D3 did not further decrease PVP in cirrhotic rats. Notably, a marked decrease in hepatic VDR and CaSR expressions was noted in cirrhotic human/rat livers compared with non‐cirrhotic human/rat livers. In cirrhotic rats, vitamin D3 administration decreasing IHR by inhibiting the renin–angiotensin system, hepatic oxidative stress, inflammation/fibrosis, angiotensin II (ANGII) production, CaSR‐mediated ANGII hyperresponsiveness, ANGII‐induced hepatic stellate cells contraction, and correcting hepatic endothelial dysfunction through upregulation of hepatic VDR, CaSR, and endothelial nitric oxide synthase expressions. Conclusion Chronic vitamin D3 treatment alone results in comparative portal hypotensive effects as propranolol alone in cirrhotic rats with PH. Taken together, chronic vitamin D3 administration was an ideal alternative strategy to effectively improve PH without unwanted systemic side‐effects.